Experience in Shaping the Legal Framework of State Policy on Combating Cybercrime in Post-Soviet Countries - Grytsyshen, Dymytrii; Sokha, Stanislav; Korzun, Svitlana (Public Policy and Accounting, 2024)
The article presents a comprehensive analysis of the experience of post-Soviet countries in shaping the legal framework of state policy on combating cybercrime. The Criminal Codes of the Republic of Uzbekistan, the Republic of Tajikistan, and Georgia are examined, with an assessment of the characteristics of these countries’ national criminal law systems in terms of establishing liability for criminal offences in the field of cybersecurity. Key attention is given to such aspects as the transnational nature of cybercrime, effective investigation of crimes committed in the global network, cooperation between law enforcement agencies of different countries, and developing national legislation on cybercrime in Ukraine. The article explores the specific features of the criminal law of the Republic of Uzbekistan, the Republic of Tajikistan, and Georgia, identifying fundamental directions for transforming Ukraine’s criminal legislation in the context of modern challenges and threats in cybercrime. The study of the legal framework for state policy on combating cybercrime in Uzbekistan, Tajikistan, and Georgia made it possible to determine the directions for transforming Ukraine’s criminal legislation to expand the types of cybercrimes and establish criminal liability for their commission.